A Novel Coagulation Classification and Postoperative Bleeding in Severe Spontaneous Intracerebral Hemorrhage Patients on Antiplatelet Therapy - Liu, Qingyuan; Li, Xiong; Wang, Nuochuan; Yang, Junhua; Wang, Kaiwen; Chen, Shanwen; Li, Jiangan; Wu, Jun; Zhang, Yanan; Wang, Shuo (Frontiers in Aging Neuroscience, 2022)
Background and Purpose For patients with severe spontaneous intracerebral hemorrhage on antiplatelet therapy (patients with APT-SICH), postoperative rebleeding (PR) is an important cause of poor outcomes after surgery. As impacted by coagulation disorder caused by APT, patients with APT-SICH are likely to suffer from PR. This study aimed to assess the risk of PR in patients with APT-SICH receiving emergency surgery using a novel coagulation classification. Methods This prospective, multicenter cohort study consecutively selected patients with APT-SICH between September 2019 and March 2021. The preoperative coagulation factor function was recorded, and the platelet function was assessed using thrombelastography. Based on platelet and coagulation factor function, a novel four-type coagulation classification, i.e., Type I (severe coagulation disorder), Type IIa (low platelet reserve capacity), Type IIb (normal coagulation), and Type III (hypercoagulation), was presented. The primary outcome was PR, defined as the rebleeding in the operative region or new intracerebral hemorrhage correlated with the operation. Results Of the included 197 patients with APT-SICH, PR occurred in 40 patients (20.3%). The novel coagulation classification categorized 28, 32, 122, and 15 patients into Type I, Type IIa, Type IIb, and Type III, respectively. The Type I patients had the highest incident rate of PR (39.3 per 100 persons), followed by the Type IIa patients (31.3 per 100 persons). In the PR-related analysis, the large hematoma volume (hazard ratio (HR): 1.02; 95% CI: 1.02–1.03; p < 0.001), Type I (HR: 9.72; 95% CI: 1.19–79.67; p = 0.034), and Type IIa (HR: 8.70; 95% CI: 1.09–69.61; p = 0.041) were correlated with the highest risk of PR. The coagulation classification could discriminate the PR patients from no PR (NPR) patients (p < 0.001), and it outperformed the conventional coagulation assessment (only considering platelet count and coagulation factor function) (c-statistic, 0.72 vs. 0.55). Conclusion The novel coagulation classification could discriminate the patients with APT-SICH with the highest risk of PR preoperatively. For the Type I and Type IIa patients, emergency surgery should be performed carefully.